COMPARATIVE ANALYSIS OF COSTS AND RETURNS OF RADISH CULTIVATION BETWEEN THE HOLE-DROPPING AND BROADCASTING METHODS OF RADISH FARMERS IN SUAN PHUENG DISTRICT RATCHABURI PROVINCE - Saruno, Yupa (Journal of Social Science and Cultural, 2025)
The research objectives were to study the cost and return of radish cultivation between the hill dropping method and the sow seeding method of radish farmers. The research was to analyze and compare the cost and the return of radish cultivation between the hill dropping method and the sow seeding method of radish farmers. The sample population was 127 radish farmers in Suan Phueng District Ratchaburi Province. The sample was selected by purposive sampling as a questionnaires research. Data were collected by using questionnaires. The results found that the cost of planting radish by hill dropping. the raw materials were 1,258.58 baht/rai, the labor costs were 3,716.67 baht/rai, the planting expenses was 7,886.87 baht/rai, the selling and administrative expenses ware 1,848.33 baht/rai, the return was 32,019.99 baht/rai, the gross profit was 19,157.87 baht/rai, the net profit was 17,309.54 baht/rai, the income at the break-even point was 9,031.34 baht/rai, payback with in period of 10 years, 11 months, and 9 days. The cost of planting radish by sow seeding method the materials was 187.92 baht/rai, the labor costs was 2,746.48 baht/rai, the planting expenses was 5,720.37 baht/rai, the selling and administrative expenses was 932.4 baht/rai, the return was 19,157.75 baht/rai, the gross profit. was 10,464.95 baht/rai, the net profit was 7,760.40 baht/rai, the income at the break-even point was 6,472.17 baht/rai and payback period were 8 years 3 days. In conclusion: the comparative analysis of planting radishes by hill dropping method has higher costs and returns than sow seeding method, namely raw materials was 4,207.3 baht/rai, the selling and administrative expenses was 915.93 baht/rai, the returns was 12,862.24 baht/rai, the gross profit was 8,692.92 baht/rai, the net profit was 9,549.14 baht/rai, the income at the break-even point was 2,559.17 baht/rai and the seeding method payback period was less than 2 years 11 months 6 days.